The Role of MAPK in Drug-Induced Kidney Injury. (12th March 2012) - Cassidy, Hilary; Radford, Robert; Slyne, Jennifer; O'Connell, Sein; Slattery, Craig; Ryan, Michael P.; McMorrow, Tara
Abstract : This paper focuses on the role that mitogen-activated protein kinases (MAPKs) play in drug-induced kidney injury. The MAPKs, of which there are four major classes (ERK, p38, JNK, and ERK5/BMK), are signalling cascades which have been found to be broadly conserved across a wide variety of organisms. MAPKs allow effective transmission of information from the cell surface to the cytosolic or nuclear compartments. Cross talk between the MAPKs themselves and with other signalling pathways allows the cell to modulate responses to a wide variety of external stimuli. The MAPKs have been shown to play key roles in both mediating and ameliorating cellular responses to stress including xenobiotic-induced toxicity. Therefore, this paper will discuss the specific role of the MAPKs in the kidney in response to injury by a variety of xenobiotics and the potential for therapeutic intervention at the level of MAPK signalling across different types of kidney disease.